EXPOSURE OF PEDIATRIC EMERGENCY PATIENTS TO IMAGING EXAMS, NOWADAYS AND IN TIMES OF COVID-19: AN INTEGRATIVE REVIEW - Isabela Dombeck Floriani; Ariela Victoria Borgmann; Marina Rachid Barreto; Elaine Rossi Ribeiro (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To analyze literature data about unnecessary exposure of pediatric emergency patients to ionizing agents from imaging examinations, nowadays and during times of COVID-19. Data sources: Between April and July 2020, articles were selected using the databases: Virtual Health Library, PubMed and Scientific Electronic Library Online. The following descriptors were used: [(pediatrics) AND (emergencies) AND (diagnostic imaging) AND (medical overuse)] and [(Coronavirus infections) OR (COVID-19) AND (pediatrics) AND (emergencies) AND (diagnostic imaging)]. Inclusion criteria were articles available in full, in Portuguese or English, published from 2016 to 2020 or from 2019 to 2020, and articles that covered the theme. Articles without adherence to the theme and duplicate texts in the databases were excluded. Data synthesis: 61 publications were identified, of which 17 were comprised in this review. Some imaging tests used in pediatric emergency departments increase the possibility of developing future malignancies in patients, since they emit ionizing radiation. There are clinical decision instruments that allow reducing unnecessary exam requests, avoiding over-medicalization, and hospital expenses. Moreover, with the COVID-19 pandemic, there was a growing concern about the overuse of imaging exams in the pediatric population, which highlights the problems pointed out by this review. Conclusions: It is necessary to improve hospital staff training, use clinical decision instruments and develop guidelines to reduce the number of exams required, allowing hospital cost savings; and reducing children's exposure to ionizing agents.